Egy kábeltelevíziós társaság vagyoni helyzetének vizsgálata (2003-2006) egy vidéki város, Mezőhegyes életében - Zsótér, Brigitta; Gálné Horváth, Ildikó; Szabóné Türkössy, Anikó (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Local Government of Mezőhegyes established Mezőhegyes Local TV Broadcasting Co. in 1997, which was sold out in 2004-ben for Bács-Kábel Ltd. How did his realization affect the company’s financial situation? Onto the finding out of this we made it financial analysis onto the period 2003-2006 relevantly. Ali the balance, ail taking the figures of the resuit statement into considération though, Ltd. the décliné of the company’s results was considérable after marketing him in 2004 year can be experienced.